SIFAT ANATOMI ROTAN TOHITI (Calamus inops Beccari) DI KAWASAN HUTAN LINDUNG GUNUNG PAPALIA DESA MATA WOLASI KECAMATAN WOLASI KABUPATEN KONAWE Anatomy Nature Tohiti Rattan (Calamus inops Beccari) in Protected Forest Area Of Papalia Mountain Mata Wolasi Village, Wolasi District, Sout Wolasi - Nurhayati Hadjar; Niken Pujirahayu; Istia Sitia Warni (Universitas Haluoleo, 2019)
ABSTRACTThe purpose of this study was to determine the nature of anatomy Tohiti Rattan (Calamus inops Beccari) that is in Protected Forest Area Mountain Springs Village Papalia Wolasi District of Wolasi Konsel. This research method using descriptive and anatomical measurements using standard IAWA (International Association Of Wood Anatomically, 2008). Vascular bundles at Rattan Tohiti network file consists of a collection vessel (metaxylem, protoxylem and phloem) and the fiber bundle. The average diameter metaxylem 233,74μm and the average diameter protoxylem 37,87μm. The proportion of cells rattan Tohiti, obtained the proportion of parenchymal cells, fiber bundle 48,93%, 39,02% metaxylem, phloem protoxylem 4,98% and 2,63%. Based on measurements of fiber dimensions Tohiti rattan, known fiber length very long 1956,52μm, classified as moderate 13,55μm fiber diameter, the average diameter of the lumen 5,62μm and an average wall thickness 4,27μm. Keywords: Rattan Tohiti, Structural Anatomy, Fiber Dimensions.